Return to Nature and Gain Self-consciousness: An Analysis of Jack London’s Consciousness of Spiritual Ecology in The Valley of the Moon - Zhu, Haiqing; Xiong, Huan (Pacific International Journal, 2022)
Abstract: With the deterioration of the global ecological environment, the thinking on ecological issues involving in Jack London’s novels has attracted more and more attention of the world. This paper attempts to interpret the profound spiritual ecological consciousness in Jack London’s The Valley of the Moon from the perspective of ecocriticism through text analysis. A study of spiritual ecology should provide an approach to the spiritual crisis by analyzing the essence of the spiritual ecology. This paper starts with analyzing the disorder of spiritual ecology including isolation from nature and loss of self-awareness, and goes further to give an analysis on Jack London’s proposal that human should return to nature and regain self-consciousness. Readers may gain some enlightenment from The Valley of the Moon and this paper.